Principal Strategies for Building a Quality-Oriented School Culture - Reti Sartika; Bukman Lian; Yasir Arafat (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examined the principal’s strategies for building a school culture oriented toward educational quality in an Indonesian public elementary school. A descriptive qualitative design was used to explore strategic planning, implementation, obstacles, and improvement efforts. Data were collected through semi-structured interviews, observation, and documentation. The principal, a school supervisor, a teacher, a school committee representative, and a student were selected purposively as key information sources. Data were analyzed through condensation, thematic display, conclusion drawing, and verification, while trustworthiness was strengthened through source and technique triangulation and member confirmation. The findings show that the principal developed quality culture through participatory planning, routine coordination, fair task distribution, academic supervision, teacher working groups, professional coaching, positive habituation, leadership by example, parental communication, and continuous evaluation. These practices strengthened discipline, collaboration, teacher responsibility, student character, and the learning environment. Implementation was constrained by differences in teacher readiness, limited digital and instructional facilities, inconsistent discipline, restricted time, uneven parental participation, and external influences on student behavior. The principal responded through persuasive guidance, peer support, educational discipline, resource optimization, stakeholder cooperation, and follow-up evaluation. The study offers an integrated view of principal strategy as a cultural improvement cycle and provides practical actions for elementary schools seeking quality development under limited-resource conditions.